Sexuality and autonomy in disability: Perceptions from Quality of Life’ workshops (Revista Rupturas, 2026)
This article presents perceptions from individuals who support people with disabilities and who have participated in the Calidad de Vida’ workshops in 2022 and 2023. The participants were parents of the San Felipe Nery and from the foundation AAGRUPERI. The aim of the article is to highlight ideas within the family of people with disabilities, \ identifying prejudices or stereotypes that negatively affect their quality of life. Experiences and perceptions regarding autonomy and sexuality in the context of disabilities are reconstructed based on the application of questionaries and systematization records. It’s identified that the prevailing notion of disability within families has characteristics of the rehabilitative model.
Keywords: Intellectual disability; independence; well-being; sexuality; workshop